Study on the Effect of Passion Fruit Leaves Tea Addition on the Quality of Black Tea - Dodi Mart Tuhu Manik; Herla Rusmarilin; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This study was conducted to investigate the effect of ratio of tea leaves and soursop leaves on the quality of tea. This study used a completely randomized design with two factors, namely ratio of  tea leaves and soursop leaves ( D ) : (20:80%, 40:60%, 60:40%, 80:20%) and withering time ( P ) : (15,16,17,18 hours). The Parameters analyzed were moisture content, tannin content, ash content, and the value of organoleptics (taste, color of water and texture) The result showed that the ratio of tea leaves and soursop leaves had highly significant effect on the moisture content, tannin content, ash content, color, taste and texture. Withering time had highly significant effect on water content, tannin content, ash content, color, taste and texture. The interaction of ratio of tea leaves and soursop leaves and withering time had a highly significant effect on the moisture content, tannin content, ash content, color, taste and texture. Ratio of soursop leaves and tea leaves 50%:50% with 18 hours withering produced the best quality of tea. Keyword : leaves of tea, soursop leaves, ratio of tea leaves and passion fruit leaves, withering time.